Die Disziplinierung der Stadt Moderner Städtebau in Zürich 1900 bis 1940 - Kurz, Daniel (gta Verlag, 2022)
The enormous growth of European cities around 1900 was disillusioning: the rapid change was experienced as chaos. Criticisms of dense neighbourhoods, overcrowded flats, unhealthy everyday life and the lack of green space in the city grew ever louder. Sweeping reform was demanded that affected urban planning and social and private existence. The vision of the garden city promised a comprehensive alternative to the European city of the past. As a result, new strongly uniform and attractive neighbourhoods emerged in both Swiss and German cities. Ideas of order and discipline, as well as visions of social justice and integration, found visible expression there. At the same time, however, public and motorized transport set in motion a dynamic that disrupted the traditional city fabric and ushered in a comprehensive separation of functions: agglomeration began to take shape. Using Zurich as an example, this book describes the twentieth-century changes to the city; it provides a compact description of social and legal conditions, theoretical positions and their practical implementation in urban planning.